Protective effect of simvastatin in the cyclophosphamide-induced hemohrragic cystitis in rats - Dantas,Anna Carolina Batista (2010)
PURPOSE: Cyclophosphamide (CYP) is an antineoplastic agent used for the treatment of many neoplastic and inflammatory diseases. Hemorrhagic cystitis is a frequent side effect of CYP. Several studies show that simvastatin has important pleiotropic (anti-inflammatory and immunomodulatory) effects. The purpose of the study was to investigate the effect of simvastatin on bladder, ureter and kidney injury caused by CYP. METHODS: Adult male Wistar rats were randomly divided into three groups. The CYP/SIM group received simvastatin microemulsion by gavage during 7 days (10 mg/kg body wt) before the administration of CYP and the CYP/SAL group rats received saline 0.9%. The control rats were not treated. After that, all rats were treated with a single dose of CYP 200 mg/kg body wt intraperitoneally. The rats were killed 24 h after CYP administration. Plasma cytokines (TNF-α, IL-1β, IL-6) were measured by ELISA. Macro and light microscopic study was performed in the bladder, kidney and ureter. RESULTS: In the bladders of CYP/SIMV treated rats edema of lamina propria with epithelial and sub-epithelial hemorrhage were lower than in CYP/SAL treated rats. The scores for macroscopic and microscopic evaluation of bladder and ureter were significantly lower in CYP/SIMV rats than in CYP/SAL rats. The kidney was not affected. The expression of TNF-α, IL-1β and IL-6 was significatly lower in CF/SINV rats (164.8±22, 44.8±8 and 52.4±13) than in CF/SAL rats (378.5±66, 122.9±26 e 123.6±18), respectively. CONCLUSION: The results of the current study suggest that simvastatin pretreatment attenuated CYP-induced urotelium inflammation and decreased the activities of cytokines.